“ Meningkatkan Minat Belajar Anak di Panti Asuhan Kasih Setia Melalui Mini Project Ilmu Kesejateraan Sosial” - Meidona Hutapea Mey; Berlianti (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
We cannot deny that the pandemic period makes children bored and bored due to the school system from home or online, it is not uncommon for children to feel lazy which causes their interest in learning to decrease, not to mention the children who are at the Kasih Setia Orphanage. The caretakers of the orphanage must think of ways to increase the children's interest in learning in the orphanage. Through PKL activities from the Social Welfare Study Program, Faculty of Social and Political Sciences, it is hoped that it will have a positive impact on children at the Kasih Setia Orphanage."The Intervention Program used in this practicum is a general intervention consisting of; Intake, Assessment and Intervention Planning, Member Selection, Group Development, Evaluation and Termination. In addition, there is an increase in reading and speaking skills and their motivation in learning English. In addition, this program also provides benefits for both parties involved (orphans and students) socially and educationally. This means that there is a significant positive impact after the implementation of this program.